2012
DOI: 10.1039/c2an35742a
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of gold nanoparticles to the signal amplification in surface plasmon resonance

Abstract: Gold nanoparticle labelling has been shown to produce a remarkable improvement in sensitivity for small molecule detection based on Surface Plasmon Resonance (SPR) bio-sensing. The LSPR (localised SPR)-SPR coupling effect and size/mass-material properties associated with gold nanoparticles are the two main factors to change the SPR resonance condition and cause the enhancement. In this paper we examine the separation of these factors in the context of a classical SPR bio-interaction assay format, and consider … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 31 publications
1
54
0
Order By: Relevance
“…However, only the ballistic photons (coherent photons reflected on material-characteristic features) which come from a certain depth are coherent with the reference beam (Mecher et al, 2002) and thus the SPR waves of the nanoparticles can interact with the reference beam of the hologram before they decay: Accordingly, it can be considered that the quantum-size effect of the optical and electronic properties of the nanoparticles (SPR) may play a role in the volume Bragg replay, this feature is supported by a study stating that a periodically ordered metal layer of nanoparticles in a medium can convert an incoming light wave to a surface Plasmon-polariton wave and vice versa (Cowan, 1972;Smirnova et al, 2009 to the in situ interaction of the nanoparticle SPR (in near IR due to aggregation) with the object beam at the moment of laser exposure resulting in the photomixing of the two waves (object and SPR) and their constructive interference with the reference beam modulation of the refractive index (Scheme 2). The SPR of the nanoparticles can travel a short distance ($ 200 nm (Hong, 2012)) and then decay; thereafter, the monochromatic replay obtained cannot be considered solely an SPR replay as the cross section of a typical hologram (dry) analyzed in this study, indicated an approximate height of 1.2 μm (SEM analysis, Supplementary material). In addition, considering a uniform fringe spacing and mass modulation, it is possible that the SPR from the nanoparticles has the same wavelength (Hong, 2012) and thus interacts consistently throughout the volume of the grating.…”
Section: Plausible Explanations For the Wavelength Shift To Near Irmentioning
confidence: 97%
See 1 more Smart Citation
“…However, only the ballistic photons (coherent photons reflected on material-characteristic features) which come from a certain depth are coherent with the reference beam (Mecher et al, 2002) and thus the SPR waves of the nanoparticles can interact with the reference beam of the hologram before they decay: Accordingly, it can be considered that the quantum-size effect of the optical and electronic properties of the nanoparticles (SPR) may play a role in the volume Bragg replay, this feature is supported by a study stating that a periodically ordered metal layer of nanoparticles in a medium can convert an incoming light wave to a surface Plasmon-polariton wave and vice versa (Cowan, 1972;Smirnova et al, 2009 to the in situ interaction of the nanoparticle SPR (in near IR due to aggregation) with the object beam at the moment of laser exposure resulting in the photomixing of the two waves (object and SPR) and their constructive interference with the reference beam modulation of the refractive index (Scheme 2). The SPR of the nanoparticles can travel a short distance ($ 200 nm (Hong, 2012)) and then decay; thereafter, the monochromatic replay obtained cannot be considered solely an SPR replay as the cross section of a typical hologram (dry) analyzed in this study, indicated an approximate height of 1.2 μm (SEM analysis, Supplementary material). In addition, considering a uniform fringe spacing and mass modulation, it is possible that the SPR from the nanoparticles has the same wavelength (Hong, 2012) and thus interacts consistently throughout the volume of the grating.…”
Section: Plausible Explanations For the Wavelength Shift To Near Irmentioning
confidence: 97%
“…The SPR of the nanoparticles can travel a short distance ($ 200 nm (Hong, 2012)) and then decay; thereafter, the monochromatic replay obtained cannot be considered solely an SPR replay as the cross section of a typical hologram (dry) analyzed in this study, indicated an approximate height of 1.2 μm (SEM analysis, Supplementary material). In addition, considering a uniform fringe spacing and mass modulation, it is possible that the SPR from the nanoparticles has the same wavelength (Hong, 2012) and thus interacts consistently throughout the volume of the grating. Moreover, due to the assumption that two different wavelengths interact, it must be expected to have a time travelling change, which although in a hologram of an object can result in image blurring, it should not make a difference for a hologram with no image display.…”
Section: Plausible Explanations For the Wavelength Shift To Near Irmentioning
confidence: 97%
“…Gold nanoparticles (40 nm) were used to conjugate endotoxins to enhance the SPR signal to detect a lower range of endotoxin concentration (Hong and Hall, 2012;Kumar et al, 2011). Gold nanoparticles (1000 mL) were activated using 5 mL NaOH (0.2 M) and mixed with 10 mL of endotoxin (1 mg mL À 1 ) then incubated on a shaker for 60 min.…”
Section: Preparation Of Endotoxin Samplesmentioning
confidence: 99%
“…The Au NP density in the vicinity of the gold surface might have an important influence as it changes the interparticle space and, consequently, the position of the LSPR wavelength as well as the surface mass and, thus, the dielectric properties of the layer next to the gold layer. This important point was recently investigated by Hong and Hall using a spectral rather than an angle resolved SPR read out (Hong and Hall 2012). They showed that the LSPR-SPR coupling effect diminishes when the spacer layer is thicker than ≈10 nm.…”
Section: Enhancement Of Spr Signalsmentioning
confidence: 99%